Managing staged policy implementation: Balancing short‐term needs and long‐term goals. (26th July 2019) - Carey, Gemma; Nevile, Ann; Kay, Adrian; Malbon, Eleanor
Abstract: This study focuses on the agency of governments engaged in implementation processes that take place over a number of years and through multiple stages. The long timeframes associated with staged implementation leave reforms vulnerable to the institutional effects that may ultimately derail policy aspirations. Governments engaged in staged implementation need to be able to plan longitudinally (foresight capacity) and analyse whether implementation processes are creating endogenous sources of institutional change and the likely impact of such change (reflective capacity). In this paper, we argue that being able to exercise foresight capacity and reflective capacity is necessary but not sufficient, if long‐term policy goals are to be realised. Governments must also be able to navigate the inconsistent objectives that arise across the different stages of an implementation process by modifying implementation approaches in ways that reduce the likelihood of unwanted implementation effects occurring—what we have labelled "mitigation capacity."